Dukungan Internal atau Eksternal; Self-Compassion dan Perceived Social Support Sebagai Prediktor Stres - Lim, Maria Theresia Astrid Felicia; Kartasasmita, Sandi (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
The purpose of this study is to find out which variable is more accurate at predicting stress caused by daily hassles in university students; self-compassion or perceived social support. Stress is a condition that arise when individuals perceive that there is a discrepancy between the experienced demands and the resources needed to fulfill these demands. Daily hassles are everyday demands or problems that are irritating, trigger frustration, and cause stress. Self-compassion is the attitude of treating yourself well, understanding, supporting, and full of compassion. Perceived social support is an individual perception that social support will be available when needed, and make individuals feel that other people love, care, and respect said individual. The participants for this study are 573 students aged 17 to 26 years. Measuring instruments used consist of the Perceived Stress Scale-10, Self-Compassion Scale, and Multidimensional Scale of Perceived Social Support. Data analysis was performed by multiple regression analysis technique. The result of the study shows several findings. First, the self-compassion variable is more accurate  at predicting stress caused by daily hassles compared to perceived social support variable. Second, the dimension of self-compassion is the strongest predictor of stress because daily hassles are the dimension of isolation. Third, the source of perceived social support that is most able to predict stress due to daily hassles is the perceived social support from friends.Tujuan dari penelitian ini adalah mengetahui variabel mana yang lebih kuat memprediksi stres yang disebabkan daily hassles pada mahasiswa; self-compassion atau perceived social support. Stres merupakan kondisi yang dihasilkan saat individu mempersepsikan bahwa terdapat diskrepansi antara tuntutan-tuntutan yang dialami dan sumber-sumber yang diperlukan untuk memenuhi tuntutan-tuntutan tersebut. Daily hassles merupakan tuntutan atau masalah sehari-hari yang menjengkelkan, memicu frustrasi, dan menyebabkan stres. Self-compassion merupakan sikap memperlakukan diri sendiri dengan baik, pengertian, mendukung, dan penuh kasih sayang. Perceived social support merupakan persepsi individu bahwa dukungan sosial akan diterima saat diperlukan, dan membuat individu merasa orang lain cinta, sayang, peduli, dan menghargai individu tersebut. Partisipan penelitian merupakan 573 mahasiswa berusia 17 hingga 26 tahun. Alat-alat ukur yang digunakan terdiri dari Perceived Stress Scale-10, Self-Compassion Scale, dan Multidimensional Scale of Perceived Social Support. Analisis data dilakukan dengan teknik analisa regresi ganda. Hasil penelitian menunjukkan beberapa hal. Pertama, variabel self-compassion lebih kuat memprediksi stres yang disebabkan daily hassles dibandingkan dengan variabel perceived social support. Kedua, dimensi self-compassion yang paling kuat memprediksi stres karena daily hassles adalah dimensi isolation. Ketiga, sumber perceived social support yang paling mampu memprediksi stres karena daily hassles adalah perceived social support yang didapatkan dari teman.